Employees' English language proficiency and visitors' perception of services received at Beijing Art Zone 798 - Selke, Raimond (Universiti Putra Malaysia Press, 2014)
This study concerns the perception of proficiency in English as a foreign language among employees in the Beijing 798 art zone plus visitors’ perception of services received and staff professionalism. The aim of the study is to establish the extent of the mismatch between the perceptions of both gallery employees and foreign visitors and of the role this plays in the overall visitor experience. Data collection comprised of a bespoke questionnaire with additional open ended questions. All questionnaires were distributed to both employees and visitors in August 2013. Based on the responses received from 100 respondents, the results showed significant misinterpretation that resulted from ineffective communication. Most visitors experienced a number of issues and faced difficulties in obtaining appropriate feedback from gallery staff. These communication problems, (relating to language barriers, either in English among local staff, or in Mandarin among overseas visitors), have lead to misunderstandings and ultimately to lower appraisals of the art works exhibited. The study offers suggestion for improvement, e.g. through the more efficient teaching of English for specific purposes, i.e. tourism, volunteering as mandatory industry training for foreign language students from nearby colleges or universities, and the extension of general information boards and signs within the art district itself. The study is limited in the number of participants (n=100) and should, therefore be repeated for higher objectivity with more participants (n>1000).